2011
DOI: 10.1016/j.socscimed.2011.06.057
|View full text |Cite
|
Sign up to set email alerts
|

An extension in eligibility for free primary care and avoidable hospitalisations: A natural experiment

Abstract: In the Republic of Ireland, approximately 30 per cent of the population ('medical card patients') are entitled to free GP services. Eligibility is determined primarily on the basis of an income means test. The remaining 70 per cent of the population ('private patients') must pay the full cost of GP consultations. In July 2001, eligibility for a medical card was extended to all those over 70 years of age, regardless of income. This extension in eligibility provides a natural experiment whereby we can examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…One US study showed that poorer access to primary care services increased EHA, but a study in Ireland showed that increasing free primary care to those patients over 70 years of age had no effect on EHA 55 56…”
Section: Resultsmentioning
confidence: 99%
“…One US study showed that poorer access to primary care services increased EHA, but a study in Ireland showed that increasing free primary care to those patients over 70 years of age had no effect on EHA 55 56…”
Section: Resultsmentioning
confidence: 99%
“…In a study in Canada, improving access to primary care resulted in a reduction in primary-care-sensitive hospitalizations among the elderly but did not change total hospitalization rates. 33 In Ireland, Nolan et al (2011) observed no changes in avoidable hospitalizations as a result of improved access to primary care. 34 A study conducted in the United States revealed that reductions in the hospitalization rate were not linked to the use of primary care services.…”
Section: Discussionmentioning
confidence: 99%
“…33 In Ireland, Nolan et al (2011) observed no changes in avoidable hospitalizations as a result of improved access to primary care. 34 A study conducted in the United States revealed that reductions in the hospitalization rate were not linked to the use of primary care services. 35 Saha et al (2007) had hypothesized, like we did, that improving access to primary care -by expanding the Medicaid programme in the state of Oregon in the United States to cover an additional 100 000 low-income families -would result in fewer hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in Iran, there was no significant difference between the rate of PHs before and after the family physician and rural insurance plan based on the Chi-square test (Salavati and Rashidian, 2017). In another study in Ireland, free access of people to urban family physicians over seventy years did not affect the burden of PHs (Nolan, 2011). However, in a study in Brazil, coverage of the family health plan for PHs had a protective effect (Carvalho et al , 2015).…”
Section: Discussionmentioning
confidence: 98%